Computational Biomaterials: Computational Simulations for Biomedicine - Dai, Xinyue; Chen, Yu (Advanced materials (Weinheim), 2023)
With the flourishing development of material simulation methods (quantum chemistry methods, molecular dynamics, Monte Carlo, phase field, etc.), extensive adoption of computing technologies (high‐throughput, artificial intelligence, machine learning, etc.), and the invention of high‐performance computing equipment, computational simulation tools have sparked the fundamental mechanism‐level explorations to predict the diverse physicochemical properties and biological effects of biomaterials and investigate their enormous application potential for disease prevention, diagnostics, and therapeutics. Herein, the term “computational biomaterials” is proposed and the computational methods currently used to explore the inherent properties of biomaterials, such as optical, magnetic, electronic, and acoustic properties, and the elucidation of corresponding biological behaviors/effects in the biomedical field are summarized/discussed. The theoretical calculation of the physiochemical properties/biological performance of biomaterials applied in disease diagnosis, drug delivery, disease therapeutics, and specific paradigms such as biomimetic biomaterials is discussed. Additionally, the biosafety evaluation applications of theoretical simulations of biomaterials are presented. Finally, the challenges and future prospects of such computational simulations for biomaterials development are clarified. It is anticipated that these simulations would offer various methodologies for facilitating the development and future clinical translations/utilization of versatile biomaterials. This review systematically introduces the achievements on computational biomaterials in biomedical applications, summarizes the computational simulation in revealing internal physicochemical mechanism behind the biomaterial, and offers an outlook on the computatinal biomaterials in nanoenabled amalgamation of chemistry, material science, biology, computational and medicine based on the reports of computational biomaterials‐involved disease diagnosis, drug delivery, disease therapies and other biomimetic biomaterials.